2014
DOI: 10.1590/0100-2945-355/13
|View full text |Cite
|
Sign up to set email alerts
|

Uso fertilizante do subproduto da agroindústria processadora de goiabas I: atributos químicos do solo

Abstract: A utilização de fontes alternativas de nutrientes, provenientes especialmente de resíduos e subprodutos da agroindústria, pode ser estratégia importante na ciclagem de elementos essenciais, garantindo destino adequado de materiais que seriam descartados. Assim, objetivou-se avaliar a aplicação de doses do subproduto da indústria processadora de goiabas sobre a fertilidade de um Argissolo, sob pomar de goiabeiras. As doses de resíduo foram estabelecidas em função dos teores de N no material. O delineamento empr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
1
8
0
5
Order By: Relevance
“…This result can be explained by the high lignin content contained in this organic waste (ZOCA et al, 2014), which hampers decomposition and humus formation in the soil. Souza et al (2014) found no changes in the organic matter content of the 0 -20 cm soil layer after five years of surface applications of rates up to 36 t ha -1 of waste generated by the guava processing industry, consisting basically of seeds of the fruit. In the 0 -5 cm layer of an area of producing coffee plants, Silva et al (2015) found a linear increase in organic C content, and consequently of soil organic matter, in response to surface applications of organic compound containing coffee husk.…”
Section: Resultsmentioning
confidence: 76%
“…This result can be explained by the high lignin content contained in this organic waste (ZOCA et al, 2014), which hampers decomposition and humus formation in the soil. Souza et al (2014) found no changes in the organic matter content of the 0 -20 cm soil layer after five years of surface applications of rates up to 36 t ha -1 of waste generated by the guava processing industry, consisting basically of seeds of the fruit. In the 0 -5 cm layer of an area of producing coffee plants, Silva et al (2015) found a linear increase in organic C content, and consequently of soil organic matter, in response to surface applications of organic compound containing coffee husk.…”
Section: Resultsmentioning
confidence: 76%
“…Com o incremento das doses do subproduto, houve aumento das concentrações de fósforo no solo ao longo dos anos, conforme relatado na Parte I deste artigo (SOUZA et al, 2014). Entretanto, esse aumento de P no solo do pomar não alterou os teores foliares de fósforo nas plantas.…”
Section: Resultsunclassified
“…Os detalhes sobre a localização da área experimental, análise química e física do solo, características do pomar, cultivar da goiabeira, análise química do subproduto da indústria processadora de goiabas, delineamento estatístico empregado, bem como os efeitos da aplicação do subproduto sobre os atributos químicos do solo estão descritos na Parte I deste artigo (SOUZA et al, 2014).…”
Section: Methodsunclassified
“…The increase in the agroindustrial activity has led to the generation of large quantities of waste in the last decades, which, when disposed in an inadequate manner, can have negative impacts on the environment (Souza et al, 2014). The composition of these residues depends on the raw material, but many of them have potential for use in agriculture, and employment according to technical criteria presents benefits, such as the supply of nutrients to the plants and the correction of soil acidity (Guimarães et al, 2012).…”
Section: Introductionmentioning
confidence: 99%